Ablasi Septal pada Pasien dengan Hypertrophic Obstructive Cardiomyopathy pada Pasien dengan Gagal Nafas - Jusuf Endang; H Haryadi; Siska Suridanda; Andika S; Roy Christian; I Irmalita; Sunu Budi Raharjo; Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2013)
Hypertrophic Obstructive Cardiomyopathy (HOCM) prevalence is about 1 among 500 population. It is caused by genetic malformation. Dyspnoe, angina pectoris and syncope are clinical manisfestation. Pharmacological and non-pharmacological treatments can be performed to relieve the obstructive symptoms. Recently alcohol septal ablation has been proven improve haemodynamic and functional status.We report a case of HOCM patient with refractory lung oedema and intubated due to respiratory failure that was immediatelly improved afterseptal ablation.